Winnicott from then to Now and the False Self (Global Journal of Medical Research, 2021)
Starting with a very small analysis of the influences of Freud (Sigmund Freud 6 may 1856 in Freiberg to 23 September 1939 in London) in the studies of psychoanalysis that were the starting point for the others (metapsychology: point of view Topic Page "Dynamic" Dynamic in conflict "Freud's studies on the switches studies of understanding its functioning and the particular external and internal actions that form the individual's psyche this initial understanding that guides all or almost every other way of conceiving of mechanism understanding these forms of internal forces of the human being Lacan said "I am Freudian you if you want to be Lacanians" curiously, we have a tendency to link studies and other things to our daily lives to aspects of our routine in the Case of Donald Woods Winnicott (Plymouth, April 7, 1896-January 28, 1971) Winnicott was a pediatrician so it is not strange that his retrieved focus is on the initial process of human development. In these developmental processes, there are many disagreement points between within the thought of psychoanalytic schools. If we think of a fact of the psychoanalyst's position, for the most part, let us say in the course of the analysis, we can say that in other schools the analyst has more of the father's position while in the Winnicottian psychoanalytic clinic the analyst for most of the course of the sessions has a mother's position.